22. KNOWLEDGE, PRACTICE OF BREASTFEEDING AND ASSOCIATED FACTORS AMONG POSTPARTUM MOTHERS AT DI LINH DISTRICT MEDICAL CENTER, LAM DONG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Assessing knowledge and practice of breastfeeding among postpartum mothers and analyzing associated factors at Di Linh District Medical Center, Lam Dong province.Methods: This is a cross-sectional study with analysis of 380 postpartum mothers at the Department of Reproductive Health and Obstetrics Care, Di Linh District Medical Center, Lam Dong Province.Results: This study shows that the proportion of research subjects with correct general knowledge about breastfeeding reached 60.3%, and correct general practice only reached 47.9%.Conclusion: There is an association between correct knowledge about breastfeeding with age group, place of residence, gender, and there is an association between correct knowledge about breastfeeding and correct practice.
Keywords: Breastfeeding; Breastfeeding practice; Breastfeeding knowledge.